Neidiomorpha gusevii—a new diatom species (Bacillariophyceae: Neidiaceae) from Southeast Asia - Glushchenko, Anton; Kociolek, John Patrick; Kuznetsova, Irina; Kezlya, Elena; Kulikovskiy, Maxim (Phytotaxa, 2019)
We present light and scanning electron microscopical observations on one new species of Neidiomorpha from Vietnam. The new species, Nediomorpha gusevii Glushchenko, Kulikovskiy & Kociolek sp. nov., is described on the basis valve outline, shape of the apices, as well as striae and areolae densities. Morphology of Neidiomorpha species, especially on the basis valve outline, is discussed. Neidiomorpha gusevii sp. nov. possesses all of the typical morphological features for the genus, including valves that have longitudinal canals with pleuriseriate coverings, constrictions about the center, rostrate apices, uniseriate striae, absence of renilimbii, straight raphe with small central pores and hooked distal raphe ends going to mantle, and lacking lacinia. Our new species is compared with other three known species from the genus Neidiomorpha, including N. binodis, N. binodiforme and N. sichuaniana. N. gusevii sp. nov. is the first species of Neidiomorpha documented with LM and SEM from Southeast Asia.